LEXICOGRAPHICAL STUDIES ON THE SOUTHWESTERN DIALECTS OF THE UKRAINIAN LANGUAGE - Vasyl Greshchuk (Vasyl Stefanyk Precarpathian National University, 2015)
The paper deals with the issue of compiling the Southwestern dialect dictionaries. A survey of the history of the dialect dictionaries from the mid-nineteenth century to the present is given. The scientific background and principles of compiling the dictionaries in question are analyzed. Special attention is given to dictionary register, dictionary entry structure, description of semantic properties of registered words, illustrative material, word passport. It has been established that many aspects of the Hutsul dialects are reflected in different lexicographical works, though a big academic dictionary still needs to be written. There exist big differential dictionaries of the Boyko, Bukovynian, Upper Dniestrian dialects. The Transcarpathian and Lemko dialects are less closely studied in this respect. There have been carried out some lexicographical studies of the Podillian, Pokuttian, Southern Volynian dialects and the dialects of the Sian river basin; further research is certainly needed to provide a firm basis for compiling dictionaries of these dialects.